2003
DOI: 10.1007/s00122-003-1412-z
|View full text |Cite
|
Sign up to set email alerts
|

First RFLP linkage map of red clover (Trifolium pratense L.) based on cDNA probes and its transferability to other red clover germplasm

Abstract: We constructed a genetic linkage map of red clover ( Trifolium pratense L., 2n=2 x=14) using RFLP markers from cDNA probes of a backcrossed mapping population, and investigated the transferability of the markers to other red clover germplasm. The map contains 157 RFLP markers and one morphological marker on seven linkage groups. The total map distance was 535.7 cM and the average distance between two markers was 3.4 cM. All of the cDNA probes of the map were hybridized to the fragments of genomic DNA from 12 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 39 publications
1
42
0
Order By: Relevance
“…Due to the conserved genomic regions between different genome, SSR marker could be transferable among congeneric species (Boutin et al 1995;Isobe et al 2003;Kuleung et al 2004). High transferability of EST-SSRs (34%) and genomic SSR (25%) between soybean and cultivated peanut were reported (He et al 2006;Hong et al 2010).…”
Section: Pcr Amplification and Polymorphism Analysismentioning
confidence: 99%
“…Due to the conserved genomic regions between different genome, SSR marker could be transferable among congeneric species (Boutin et al 1995;Isobe et al 2003;Kuleung et al 2004). High transferability of EST-SSRs (34%) and genomic SSR (25%) between soybean and cultivated peanut were reported (He et al 2006;Hong et al 2010).…”
Section: Pcr Amplification and Polymorphism Analysismentioning
confidence: 99%
“…The first genetic linkage map with 256 restriction fragment length polymorphism (RFLP) markers was constructed for red clover by Isobe et al (2003) using a mapping population of 188 F 1 individuals derived from a double pseudo-testcross between HR as the female parent and R130 as the male parent. HR was an elite plant selected from early progenies of the cross between Hokuseki and a Swiss variety Renova with characteristics of early flowering, erect shape, red flower colour, and middle-sized leaves.…”
Section: Dna Marker Systems and Genetic Mapsmentioning
confidence: 99%
“…Such a population of red clover useful for segregation analysis, interval mapping, and QTL investigation was constructed by Isobe et al (2003). A mappingbased approach was used to identify SSRs closely linked to the GSI-locus (Riday & Krohn 2010).…”
Section: Candidate Gene Identificationmentioning
confidence: 99%
“…They are less optimal compared to textbook F 2 populations derived from a F 1 hybrid of two inbred grandparents, since not all the parental polymorphisms are informative in terms of linkage in the progeny. The first red clover linkage map was constructed by Isobe et al [38], and contained 158 RFLP loci. Subsequently, a high density map with 1399 markers consisting of mainly SSRs and RFLPs was published [39].…”
Section: Genetics and Breedingmentioning
confidence: 99%
“…The map of Hermann et al [40] was used in a study of seed yield components, in which 38 QTL were identified. More recently, the maps of Isobe et al [38], Sato et al [39] and Hermann et al [40] were combined with three other maps to generate an integrated map consisting of 1804 markers distributed over the 7 linkage groups and a total length of 836 cM [42]. Two recent papers have described work on QTL directly linked to persistence and its component traits.…”
Section: Genetics and Breedingmentioning
confidence: 99%